Geometry-Based Stochastic Modeling for MIMO Channel in High-Speed Mobile Scenario - Binghao Chen; Zhangdui Zhong (International Journal of Antennas and Propagation)
The geometry-based stochastic channel models are proposed in this paper for the terrain cutting, suburb, and urban scenarios in high-speed railway. First, the special scenarios in high-speed railway are described. And the channel models based on the geometry scenarios are introduced. Some channel parameters are based on measurement data. Then, the space-time correlation functions in analytical form are obtained in suburb and urban scenarios. Finally, the space correlation characteristics in three scenarios are compared.